Growth and Yield Variability Performance in Ten Genotype of Tomatoes (Lycopersicum esculentum Mill ) - Wahyurini, Endah; Suryawati, Ami (RSF Conference Series: Engineering and Technology, 2022)
Efforts Availability of pest-resistant tomatoes, sweet taste, long-lasting fruit, is largely determined by the availability of various genetic sources of tomatoes and breeding methods. This study aims to determine the growth and yield of several tomato genotypes and to determine genotypes that have superior characters as a source of genes for crosses. The research method was a completely randomized design (CRD) with a single factor and three replications. The treatments consisted of 10 F1 hybrid tomato varieties, namely: Servo, Tymoti, Corona, Gustavi, Betavila, Marina, Biromaru, Bareto, Permata, and Ayuni. Observation parameters include: plant height, stem diameter, leaf shape, fruit shape, fruit color and sweetness level. The data obtained were analyzed using the analysis of variance (Anova), then the DMRT test was performed. The results showed that the genotype had a significant effect on plant height 4 and 5 mst. Gustavi tomatoes have a tall character, oval fruit shape. Bareto tomatoes have a high level of sweetness, round fruit shape, so they have high yield potential and are potential sources of genes for high production.